2011
DOI: 10.4269/ajtmh.2011.10-0654
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Infestation and Dengue Virus Infection in Aedes aegypti Females in Schools in Mérida, México

Abstract: We determined abundance of Aedes aegypti mosquitoes and presence of dengue virus (DENV) in females collected from schools in Mérida, México, during 2008 and 2009. Backpack aspiration from 24 schools produced 468 females of Ae. aegypti and 1,676 females of another human biter, Culex quinquefasciatus. Ae. aegypti females were collected most commonly from classrooms followed by offices and bathrooms. Of these females, 24.7% were freshly fed. Examination of 118 pools of Ae. aegypti females (total of 415 females) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 47 publications
(52 reference statements)
4
55
2
1
Order By: Relevance
“…We also focused on individuals who reported visiting at least one other household because we could only assess exposure in houses with participants who agreed to provide blood samples. Exposure could occur wherever infectious mosquitoes are present (44)(45)(46). In Iquitos, people commonly visit other residences, but in other geographic areas, people may be more or less mobile, making the home or other locations comparatively more important for transmission.…”
Section: Discussionmentioning
confidence: 99%
“…We also focused on individuals who reported visiting at least one other household because we could only assess exposure in houses with participants who agreed to provide blood samples. Exposure could occur wherever infectious mosquitoes are present (44)(45)(46). In Iquitos, people commonly visit other residences, but in other geographic areas, people may be more or less mobile, making the home or other locations comparatively more important for transmission.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti is the primary mosquito vector. 9,22,25,26 Study areas were identified for similarity in potential study homes, e.g., cement construction, size, and design, typically found in fraccionamiento neighborhoods, which are comprised of high-density and lowincome housing. Homes with more than one story, more than 10 windows, less than four inhabitants, or no children 15 years of age were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21] Because of the endophilic nature of Ae. aegypti, tools or approaches to exclude it from the epidemiologically most significant points of contact with humans, the home and other frequently used indoor environments, such as schools or workplaces, 9,22 would be an important addition to the armamentarium for dengue control. This type of intervention theoretically not only prevents DENV-infected female mosquitoes from entering homes and other indoor environments, such as schools or workplaces, but also prevents mosquitoes from feeding indoors on viremic humans, including while they are recuperating in the home, and then transmitting the virus to other humans frequenting the domicile.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that 16.1% of the Ae. aegypti females that were collected from Mexican schools were infected with DENV (García-Rejón et al 2011). In Brazil, previous studies showed that 17% of the Ae.…”
Section: Simplexa™ Dengue Real-time Rt-pcr -mentioning
confidence: 99%